Pantothenate Kinase Associated Neurodegeneration: A Case Report - Rahar, S; Chaudhary, A (Journal of Nepal Paediatric Society, 2012)
Pantothenate kinase-associated neurodegeneration (PKAN) is a form of neurodegeneration with brain iron accumulation (NBIA), formerly called Hallervorden-Spatz syndrome. PKAN is the first described inborn error of coenzyme A metabolism. PKAN encompasses two clinical subtypes, classic and atypical. We here report an eight year girl diagnosed as classic PKAN. We also review the literature about PKAN. Key words: Eye of tiger sign; NBIA; Neuroregeneration; Iron Accumulation; Hallevorden Spatz Syndrome DOI: http://dx.doi.org/10.3126/jnps.v32i1.5333 J. Nepal Paediatr. Soc. Vol.32(1) 2012 90-92